THE ROLE OF TEACHER NONVERBAL COMMUNICATION IN THE EFL CLASSROOM (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Successful teaching and learning in English as a Foreign Language (EFL) courses depend on efficient communication. However, students' weak language skills frequently make it difficult for them to fully participate in class discussions and comprehend spoken input. Nonverbal communication from teachers is crucial in this situation. This article looks at how teachers' nonverbal cues, including posture, eye contact, facial expressions, gestures, and classroom movement, affect students' comprehension and engagement in EFL classes. The study illustrates that intentional nonverbal communication improves comprehension, lowers learner fear, and promotes active engagement by drawing on pre-existing theoretical frameworks and a small-scale classroom observation. Pedagogical consequences for EFL teachers and teacher education programs are discussed in the article's conclusion.